The Magic of the New: How Job Changes Affect Job Satisfaction - Clemens Hetschko; Adrian Chadi (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
We investigate a crucial event for job satisfaction: changing the workplace. For representative German panel data, we show that the reason why the previous employment ended is strongly linked to the satisfaction with the new job. When workers initiate a change of employer, they experience relatively high job satisfaction, though only in the short-term. To test causality, we exploit plant closure as exogenous trigger of job switching and find no causal effect of job changes on job satisfaction. Our findings concern research on workers well-being as well as labor market and human resource policies.
Keywords: I31; J28; J63; 330